Directed Evolution of Selective Enzymes: Catalysts for Organic Chemistry and Biotechnology. Von Manfred T. Reetz. (29th March 2019) - Kries, Hajo
Abstract : Wiley‐VCH, Weinheim, 2016. 308 S., geb., 139.00 €.—ISBN 978‐3‐527‐31660‐1